The Effectiveness of Antenatal Class Education on Improving Maternal Preparedness in Facing Postpartum Hemorrhage - Azizah, Nur; Sinuhaji, Lidya Natalia; Sinaga, Rosmani; Surbakti, Imran Saputra (Open Access Health Scientific Journal, 2025)
Background: Postpartum hemorrhage (PPH) remains a leading cause of maternal mortality globally and in Indonesia. A key contributing factor is the lack of maternal preparedness in recognizing danger signs and responding promptly. Antenatal education, particularly through structured programs such as the Pregnant Women Class, is a strategic intervention to enhance maternal knowledge and readiness. This study aimed to determine the effectiveness of antenatal class education in improving maternal preparedness in facing postpartum hemorrhage in Bangun Rejo Village in 2025.Methods: A pre-experimental study using a one-group pretest-posttest design was conducted in Bangun Rejo Village from May to June 2025. Thirty third-trimester pregnant women were selected through purposive sampling. Participants attended a 90-minute antenatal class session focused on postpartum hemorrhage, delivered through lectures, discussions, and visual media. Preparedness was measured using a standardized questionnaire before and one week after the intervention. Data were analyzed using the Paired T-Test with a significance level of p < 0.05.Results: The mean preparedness score increased from 62.40 (±8.215) before the intervention to 78.73 (±6.542) after, with a mean difference of 16.33 (±7.49). The statistical analysis showed a significant improvement (p = 0.000). Additionally, the number of mothers with high preparedness increased from 0% to 73.3% post-intervention.Conclusion: Antenatal class education significantly improves maternal preparedness to face postpartum hemorrhage. This intervention enhances not only knowledge but also awareness, decision-making ability, and proactive behavior among pregnant women. It is recommended to integrate such educational strategies more broadly into maternal health services to reduce preventable maternal deaths.